Antiphospholipid Antibodies and Antiphospholipid Syndrome during Pregnancy: Diagnostic Concepts - Levy, Roger A.; dos Santos, Flavia Cunha; de Jesús, Guilherme R.; de Jesús, Nilson R. (Frontiers in Immunology, 2015)
Antiphospholipid syndrome (APS) comprises of a wide spectrum of clinical and obstetric manifestations linked to the presence of antiphospholipid antibodies (aPL). APS was described in the context of lupus, and later as an isolated syndrome or primary APS. The presence of aPL, especially the lupus anticoagulant test, is associated with adverse pregnancy outcomes, such as fetal death, recurrent early miscarriages, pre-eclampsia, and placental insufficiency, but does not seem to influence infertility. High quality scientific data to support these associations, however, are lacking, and controversies arise about the definition of positive aPL (low vs medium-high titers) or even the definition of the adverse events. This review discusses APS classification criteria and the current debate about it.